2016
DOI: 10.1371/journal.pcbi.1004836
|View full text |Cite
|
Sign up to set email alerts
|

Detecting Presymptomatic Infection Is Necessary to Forecast Major Epidemics in the Earliest Stages of Infectious Disease Outbreaks

Abstract: We assess how presymptomatic infection affects predictability of infectious disease epidemics. We focus on whether or not a major outbreak (i.e. an epidemic that will go on to infect a large number of individuals) can be predicted reliably soon after initial cases of disease have appeared within a population. For emerging epidemics, significant time and effort is spent recording symptomatic cases. Scientific attention has often focused on improving statistical methodologies to estimate disease transmission par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
103
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 76 publications
(104 citation statements)
references
References 72 publications
(87 reference statements)
1
103
0
Order By: Relevance
“…In addition, they were missing in New Caledonia, which leads to strong correlation between our estimation of the observation rate and the fraction of the population involved in the epidemic. Because of the high proportion of asymptomatic or mildly symptomatic cases, the magnitude of the outbreaks is difficult to evaluate without precise seroprevalence data (Metcalf et al, 2016) or detection of mild, asymptomatic or pre-symptomatic infections (Thompson et al, 2016). Considering vectors, no demographic data were available and this partly explains the large variability of our R0 estimations.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, they were missing in New Caledonia, which leads to strong correlation between our estimation of the observation rate and the fraction of the population involved in the epidemic. Because of the high proportion of asymptomatic or mildly symptomatic cases, the magnitude of the outbreaks is difficult to evaluate without precise seroprevalence data (Metcalf et al, 2016) or detection of mild, asymptomatic or pre-symptomatic infections (Thompson et al, 2016). Considering vectors, no demographic data were available and this partly explains the large variability of our R0 estimations.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, the rapid spread of infectious agents such as Zika virus and Ebola have led to public health incidents throughout the world. High-sensitivity detection is critical for early diagnosis of infectious diseases, with presymptomatic identification helpful for monitoring, forecasting, and ideally limiting epidemics in the early stages of an outbreak (20). Preferably, testing would be done rapidly, inexpensively, and at the point of care.…”
Section: Discussionmentioning
confidence: 99%
“…Recent work has shown that adaptive sampling can improve the efficiency of management of some diseases (Parry 2014; Parnell 2014, 2017); however, effective control requires detailed, intensive sampling of host populations which may not be showing symptoms (Cunniffe et al 2016). The distinction between severe, explosive invasions and minor outbreaks which require less expensive intervention is challenging (Thompson et al 2016). Foundational research on both theoretical and actual population dynamics on a landscape scale is essential.…”
Section: Foundational Research Needs Opportunities and Challengesmentioning
confidence: 99%